A novel function of Drosophila eIF4A as a negative regulator of Dpp/BMP signalling that mediates SMAD degradation. - Li, J.; Li, W.X. (Nature Cell Biology, 2006)
Signalling by the TGF-beta superfamily member and BMP orthologue Decapentaplegic (Dpp) is crucial for multiple developmental programmes and has to be tightly regulated. Here, we demonstrate that the Drosophila Dpp pathway is negatively regulated by eukaryotic translation initiation factor 4A (eIF4A), which mediates activation-dependent degradation of the Dpp signalling components Mad and Medea. eIF4A mutants exhibit increased Dpp signalling and accumulation of Mad and phospho-Mad. Overexpression of eIF4A decreases Dpp signalling and causes loss of Mad and phospho-Mad. Furthermore, eIF4A physically associates with Mad and Medea, and promotes their degradation following activation of Dpp signalling in a translation-independent manner. Finally, we show that eIF4A acts synergistically with, but independently of, the ubiquitin ligase DSmurf, indicating that a dual system controls SMAD degradation. Thus, in addition to being an obligatory component of the cap-dependent translation initiation complex, eIF4A has a novel function as a specific inhibitor of Dpp signalling that mediates the degradation of SMAD homologues.